2021
DOI: 10.1007/s40121-021-00456-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy and Safety of Vancomycin, Linezolid, Tedizolid, and Daptomycin in Treating Patients with Suspected or Proven Complicated Skin and Soft Tissue Infections: An Updated Network Meta-Analysis

Abstract: Introduction: Skin and soft structure infections (SSTIs) caused by methicillin-resistant Staphylococcus aureus (MRSA) pose serious health risks and cause significant cost burdens, and a conclusive recommendation about antibiotics has not yet been generated. Therefore, we performed this updated network meta-analysis to determine the preferred drug for the treatment of MRSA-caused SSTIs. Methods: We searched PubMed, Embase, and Cochrane Library to identify any potentially eligible randomized controlled trials (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…These results contrast with our research results. In 2021, Feng et al performed a NMA to evaluate the effectiveness and safety of vancomycin, linezolid, daptomycin, and tedizolid in the skin and soft tissue infection; the results of this study were consistent with ours (Feng, et al 2021). The study by Feng et al assessed drug-related severe and adverse reactions without distinguishing hepatotoxicity, nephrotoxicity, and thrombocytopenia.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…These results contrast with our research results. In 2021, Feng et al performed a NMA to evaluate the effectiveness and safety of vancomycin, linezolid, daptomycin, and tedizolid in the skin and soft tissue infection; the results of this study were consistent with ours (Feng, et al 2021). The study by Feng et al assessed drug-related severe and adverse reactions without distinguishing hepatotoxicity, nephrotoxicity, and thrombocytopenia.…”
Section: Discussionsupporting
confidence: 85%
“…The study showed that MRSA prevalence ranged from 0-73% at 19 sites in the Asia-Paci c region from 2000 to 2016 (Lim, et al 2019). Recently, the rate of MRSA infection has been increasing sharply (Feng, et al 2021), posing a challenge to the health system in terms of di cult therapy, extended length of hospital stay, expanded health costs, and high mortality (Feng, et al 2021;Jones, et al 2020). Pneumonia has gained immense attention in the medical eld because of its high mortality and complex therapeutic management (Jones, et al 2020;Torres, et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its interaction with selective serotonin reuptake inhibitors and serotonin and norepinephrine reuptake inhibitors was found to be minimal [22]. A recent meta-analysis assessing the clinical and microbiological successes of tedizolid vs. linezolid showed no significant difference between the two drugs [35 ▪ ]. In addition, tedizolid was tolerated and caused less optic and peripheral neuropathy, gastrointestinal side effects and myelosuppression/thrombocytopenia than linezolid [36,37].…”
Section: Oral Antibiotic Therapy For the Treatment Of Methicillin-res...mentioning
confidence: 99%